The Packaging Process Improvement in MSME's by Utilizing Packaging Machine Technology and Product Packaging Redesign: Perbaikan Proses Pengemasan di UMKM dengan Pemanfaatan Teknologi Mesin Pengemasan dan Desain Ulang Kemasan Produk - Ari Pranata Primisa Purba; Nofan Hadi Ahmad; Agung Kurnia Yahya; Miftahurrahmah; Tosty Maylangi Sitorus; Anang Baharuddin Sahaq (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
The understanding and compliance with the regulations of the Drug and Food Supervisory Authority (BPOM) in the food industry, especially for Micro, Small and Medium Enterprises (MSMEs) in Indonesia should be a concern for entrepreneurs so that the products produced are acceptable to modern society today. The packaging process is one of the efforts to maintain the quality, safety and hygiene of products, also as a medium of promotion and information of products marketed to consumers. MSMEs Kampioen becomes an object in the community service activities carried out by the Team of Polytechnic ATI Padang due to the eligibility of partners and business permits that already meet the existing legality. Observations and interviews were conducted to find out the obstacles experienced by MSMEs. The obstacles facing MSMEs are products that have not yet been able to compete to the supermarket because the unqualified packaging of supermarkets and BPOM. The packaging machines used are old enough and almost broken. In this context, the graphical design of packaging that meets BPOM standards and the use of Continuous Band Sealer technology is an important factor in improving competitiveness and market access for MSME. These activities ensure the benefits of accompanying activities, such as improved efficiency and production safety, improved understanding of business management, finance, and marketing, and expansion of marketing. Thus, these activities provide practical guidance and specific solutions to help MSMEs boost growth and competitiveness in the food industry sector.